Does cardiovascular autonomic dysfunction contribute to fatigue in myasthenia gravis? - Elsais, A; Kerty, E; Russell, K; Toska, K (Physiological research, 2022)
Myasthenia gravis (MG) is an autoimmune disease characterized by fatigable muscle weakness. Despite full spontaneous or pharmacological remission some MG patients still complain of physical and mental fatigue. Fatigue has been related to autonomic dysregulation. The aim of this study was to assess autonomic responses in a group of MG patients in complete remission but complaining of persistent fatigue. Seventeen well-regulated but persistently fatigued MG patients and 17 individually matched controls underwent echocardiography assessing systolic and diastolic heart function. Beat to beat cardiovascular responses at rest and to 30o head-up tilt, tilt-back, and 2-min static handgrip contraction were recorded. Fatigued MG patients had a statistically significant higher resting HR than their matched controls (p=0.03). The difference in resting heart rate between MG patients not using acetylcholine esterase inhibitors (AChEi) and their matched controls was even more pronounced (p=0.007). The autonomic cardiovascular adjustments to head-up tilt, tilt-back and handgrip contraction were not statistically significant different between patients and controls. We found a higher resting heart rate in all well-regulated but fatigued MG patients compared with controls. The difference was more pronounced between patients not taking AChEi compared to their matched controls. This finding may reflect a disturbed resting sympathovagal balance and this might be a contributing factor to the fatigue symptoms.
Keywords: krevní tlak; síla ruky; srdeční frekvence; Hand Strength; lidé; nemoci autonomního nervového systému; autonomní nervový systém; Blood Pressure; Autonomic Nervous System Diseases; Heart Rate; Autonomic Nervous System; myasthenia gravis; Myasthenia Gravis; Humans